Możliwości telefonii komórkowej i zastosowanie jej w przedsiębiorstwie - Idzikowski, Maciej; Laska, Maciej; Wasiak, Jędrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
In the paper, up-to-date and future cellular telephony technologies in mobile processing and possibilities of application in enterprise aspect are analysed. Due to wide range of presented solutions, possible applications of individual ones and integration of one another are pointed. Furthermore, wireless data transfer methods with making use of various media types, devices and basic communication software are described. Finally comparisons of individual techniques with each other are made and possible applications of them are discussed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 296-305